An Analysis of The Relevance of The Pancasila Learner Profile in The Learning of Biology - Chastanti, Ika; Rofieq, Ainur; Huda, Atuk Miftachul; Eriyanti, Ribut Wahyu; Hasruddin, Hasruddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2024)
Pancasila education is relevant to biology learning because it helps in the development of the Pancasila Learner Profile, which includes characteristics such as critical thinking and creativity. The purpose of this study was to analyse the relevance of Pancasila Learner Profile in biology learning and the challenges in integrating Pancasila values in biology learning. This research uses descriptive method with the sample being students of grade XII of SMA Negeri 1 Aek Kuo, SMA Negeri 1 Rantau Selatan and SMA Negeri 2 Rantau Selatan. Data collection was done through interview and observation. The sampling technique used in this research is purposive sampling because this school has implemented an independent curriculum. The results showed that for the dimension of faith, fear of God and noble character, students are required to pray before and after learning, the dimension of global citizenship, students are divided into groups to conduct experiments, the dimension of mutual cooperation, students carry out greening activities to preserve the environment. The independent dimension, students work independently on biology tasks, the critical thinking dimension, students solve problems that arise during experiments, and the creative dimension, students produce work from recycling waste.